Case Report: Sequential treatment with rituximab and belimumab in a pediatric patient of type 1 diabetes mellitus complicated with systemic lupus erythematosus - Li, Fangfang; Zhang, Yuci; Yin, Jing; Zhao, Linsheng; Li, Chongwei (Frontiers in Pediatrics, 2025)
Type 1 diabetes mellitus (T1DM) and systemic lupus erythematosus (SLE) are both autoimmune diseases influenced by multiple genetic and environmental factors, but rarely coexist. This case describes a 13-year-old girl with early onset of T1DM who was diagnosed with SLE 12 years later, highlighting diagnostic and therapeutic challenges, particularly in distinguishing kidney involvement and management without exacerbating hyperglycemia. The patient presented with edema of the eyelids and lower limbs. Urinalysis revealed hematuria and proteinuria. High-titer antinuclear antibody and anti-double-stranded DNA were detected. SLE was diagnosed clinically. As T1DM and SLE both cause kidney damage, kidney biopsy was performed. Deposition of various immune complexes led to a diagnosis of lupus nephritis. To avoid the impact of steroid pulses on glycemic control, conventional dose of steroids with sequential treatment with rituximab and belimumab was initiated. The combined therapy effectively alleviated the SLE condition, reduced steroids dosage, and led to discontinuation of steroids after 13 months. However, due to the prolonged disease course of T1DM, the pancreatic cell function was not reversed.